Eugenia pipensis, a new species of Eugenia sect. Umbellatae (Myrtaceae) from northeastern Brazil - Lima Lourenço, Ana Raquel (Phytotaxa, 2013)
A new species of Eugenia from the Atlantic rainforest of Rio Grande do Norte is described as Eugenia pipensis. The species is close to E. astringens, but differs by having calyx lobes 2.5 to 3 mm long and glandulose-verruculose fruits.